The formation of psychic distance : the case of Finnish managers in India - Dutta, Debashri Mishel (My University, 2015)
Purpose: The purpose of this study is to understand the formation of psychic distance and bring clarity to the variations and disagreements that abound in the literature. The aim of this thesis is also to clarify the nature of psychic distance, its key components and measurement methods, and finally to explore the formation of psychic distance in the context of developed country managers doing business in a developing country. Design/Methodology/Approach: This study has adopted the semi-structured interview method in which four Finnish managers who had direct involvement in setting up their firms in India were interviewed. The managers came from different industrial backgrounds and through the interviews provided insight into their experiences and the environment. Findings: The findings confirm that psychic distance is fundamentally a subjective concept that is best approached in combination with objective factors. Networks and experience did not play a very big role in reducing PD as indicated in literature. Other factors like values, attitudes and goals were important in coping with difficulties. It also emerged that the degree of involvement of the manager in managing daily operations impacts the experience of PD and that the dimensions of awareness and understanding are more important that simply considering objective and subjective factors. Research limitations/implications: The small number of managers interviewed, and the lack of variation in the forms of business organization is an important limitation. A lack of generalizability is also inherent in this study. Practical implications: This paper provides a good insight into the factors that may impact a manager in doing business in a foreign country and cautions the manager against assuming that information is accurate and reliable. Managers must focus more on awareness, the competitiveness of their products and services, and must develop networks. They must also develop the ability to cope with difficult standards of living and different cultural attitudes through respect, trust, transparency and developing mutual goals. Originality/Value: The research contributes greatly towards demystifying the nature of PD and its measurement. It also explores PD in the rarely studied context of developed country managers in a developing country.
Keywords: psychic distance; developing country; Finland; India; awareness; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|